TV viewers receiving: concept and studies - bouhila, redouane (Journal of Social Sciences and Humanities, 2021)
The influence exerted by the media by providing the audience with information that many rely on as motives for behavior and up to modern approaches that take the ethnographic approach as an important tool for studying the audience and revealing its various behaviors, but to know the current stakes that are relevant to the audience studies and the receiving studies in particular, it is necessary to return And recall some of the work done nearly half a century in the field of media audience studies ,so receiving studies in the field of media in general and television in particular, are a contribution of those precursors in the German theory of influence and acceptance on the one hand, and on the other hand is the result of the development of research in the field of mass communication, which has arisen by causing a break with the dominant model in the forties « Lazersfield's model of media influences », so the new approach that began in the 1980s, such as David Morley, is a different approach that focuses on the way in which Individuals translate what they receive from media messages, and the purpose of this approach is to analyze the Receiving process (TV viewing) And as a process to establish the semantics by the audience, in other words, modern studies - whose origins are derived from cultural studies - have focused on the receiving audience as a more active recipient by focusing its attention on several very important issues, watching television is a group of activities of a social and cultural form, part of which relates to the rhetorical meaning, and TV viewers are creative and effective, they do not accept simply and without criticism of the textual meanings, but rather deal with it through their previously acquired cultural capabilities and skills, moreover, the texts do not materialize One set of meanings free from ambiguity or ambiguity but rather has multiple meanings and then the members of the audience are real actors as the constituents of the audience will deal differently with different textual meanings and therefore they are called an active audience.